Springback Analysis of Elliptical Sectioned bar of Non linear Work-Hardening Materials under Torsional Loading - Lal R.K.; Dwivedi J.P.; Singh V.P. (My University, 2025)
This paper deals with the springback problems of elliptical section bars of non-linear work-hardening materials under the torsional loading. Using the deformation theory of plasticity, a numerical scheme based on the finite difference approximation has been proposed. The growth of the elastic-plastic boundary and the resulting stresses while loading, and the springback and the residual stresses after unloading are calculated. © 2017 Elsevier Ltd.